Bridging Healthcare Disparities for LGBTQ+ Community: A Zonal Study on Medical Students' Attitudes and Knowledge in India - Anjali Mediboina; Paras R. Waghmare; Harshita; Akanksha Mahajan; Ujwala Ukey (University Library System, University of Pittsburgh, 2023)
BACKGROUND: The LGBTQ+ community has long endured discrimination worldwide. This marginalized group faces significant health disparities resulting from a lack of inclusion in medical curricula, inadequate training of healthcare professionals, and negative attitudes towards their unique health needs. Such factors may contribute to a hesitancy among medical students to provide appropriate care for LGBTQ+ patients. Understanding the regional nuances can further help guide the development of region-specific educational and sensitization programs for healthcare professionals. Thus, this study seeks to assess attitudes and knowledge of medical students and interns towards the LGBTQ+ community in different zones of India (North, South, and West), and understand the variations across regions, and determine any associated demographic factors influencing the same. METHODS: Respondents were invited to participate in this cross-sectional observational study between June and November 2020 through social media platforms. They were requested to complete a self-administered questionnaire distributed via Google Forms, which was divided into three sections: the first collected demographic data, the second comprised 10 true or false knowledge-based questions, and the third contained an additional set of 10 questions using a 5-point Likert scale to assess participants' attitudes. Associations between attitudes, knowledge, and demographic characteristics were assessed using Chi-square tests (p < 0.05). RESULTS: A total of 862 responses from three zones - North, South, and West - were included in the study. Responses from the East zone were excluded due to the limited number. Among the respondents, 65.4% exhibited an overall positive attitude towards the LGBTQ+ community. Attitudes and demographics showed a statistically significant association, indicating that respondents under the age of 20, female, and medical students were more likely to hold positive attitudes across all three zones. Regarding knowledge, 56.1% of the participants demonstrated overall satisfactory knowledge levels. Knowledge and demographics were found to have a significant association, specifically concerning age and profession, but not gender. However, the zonal analysis revealed that the significant association between knowledge and demographics was only present in the South zone, while the North and West zones did not show significant associations. These findings suggest that factors other than age and profession may be influencing knowledge levels in the North and West zones. CONCLUSION: The present study provides valuable insights into the attitudes and knowledge of medical students and interns towards the LGBTQ+ community in different zones of India - North, South, and West. Despite certain limitations, such as a lower participation rate among interns and the absence of exploring religious affiliations, the findings show a significant proportion of positive attitudes and satisfactory knowledge towards the LGBTQ+ community, reflecting a growing acceptance and empathy among future healthcare professionals. However, the pronounced zonal differences in the responses must be acknowledged, and highlights the importance of region-specific interventions and targeted educational initiatives to enhance knowledge levels in the North and West zones. It is crucial to update the medical curriculum to incorporate comprehensive LGBTQ+ education and provide training and sensitization that ensures optimum care for individuals regardless of their sexual orientation and gender identity.